(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
In the work of compounds of the N-acylaminoacids with metals (Co, Mg, Ni, Mn, Zn) were synthesized. The compounds were isolated in solid state, elemental composition and physical-chemical properties were determined.